Select the product of (3x - 1)(3x - 1).

Question

Asked 11/30/2014 9:17:24 PM

Updated 11/30/2014 9:54:25 PM

1 Answer/Comment

Flagged by andrewpallarca [11/30/2014 9:54:18 PM]

s

Question

Asked 11/30/2014 9:17:24 PM

Updated 11/30/2014 9:54:25 PM

1 Answer/Comment

Flagged by andrewpallarca [11/30/2014 9:54:18 PM]

Rating

8

(3x - 1)(3x - 1)

= 9x^2 - 3x - 3x + 1

= 9x^2 - 6x + 1

= 9x^2 - 3x - 3x + 1

= 9x^2 - 6x + 1

Added 11/30/2014 9:54:25 PM

This answer has been confirmed as correct and helpful.

Select the product of (3x - 4)(2x + 8).

Question

Updated 11/30/2014 9:16:53 PM

1 Answer/Comment

(3x - 4)(2x + 8)

= 6x^2 + 24x -8x - 32

= 6x^2 + 16x - 32

= 6x^2 + 24x -8x - 32

= 6x^2 + 16x - 32

Added 11/30/2014 9:16:47 PM

This answer has been confirmed as correct and helpful.

Select the product of (3x - 4)(2x + 8). **Weegy:** (3x - 4)(2x + 8)
= 6x^2 + 24x - 8x - 32
= 6x^2 + 16x - 32 (More)

Question

Expert Answered

Updated 11/30/2014 9:55:07 PM

0 Answers/Comments

Select the product of (7x + 1)(7x - 1). **Weegy:** (7x + 1)(7x - 1)
= 49x^2 - 7x + 7x - 1
= 49x^2 - 1 (More)

Question

Expert Answered

Updated 11/30/2014 9:53:52 PM

0 Answers/Comments

Simplify the following expression. (x + 8)^3 **Weegy:** May i know what the question is? (More)

Question

Not Answered

Updated 12/1/2014 2:52:04 AM

1 Answer/Comment

Select the product of (6x + 9)(x2 - 3x + 3). **Weegy:** (6x + 9)(x^2 - 3x + 3)
= 6x^3 - 18x^2 + 9x^2 + 18x - 27x + 27
= 6x^3 - 9x^2 - 9x + 27 (More)

Question

Expert Answered

Updated 11/30/2014 9:52:33 PM

0 Answers/Comments

34,450,808

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 626 [Total 6499] Ratings 11 Comments 516 Invitations 0 Offline

There are no comments.